Leaders Circle In Facilitating School Heads' Instructional Supervision Practices For Continuing Professional Development - Joel Potane; isabel Anne M. Alano; Braziel L. Ongcachuy (International Journal of Educational Management and Innovation, 2023)
Instructional supervision is the process of ensuring that a school's educational mission is carried out by supervising, equipping, and empowering teachers to provide students with meaningful learning experiences. The study explored school heads' instructional supervision practices for continuing professional development through Leaders' Circle via a learning management system, which provides school leaders with opportunities to communicate, collaborate, critically think, be creative, and share experiences related to instructional supervision. The process owners of the instructional supervision process encountered a problem that they resolved using the Continuous Improvement (CI) learning cycle. The participants were chosen based on the prioritization matrix. Asynchronous style via Schoology and face-to-face sessions were used. The data collection tools for this study were the leaders circle manual, in-depth interviews (IDIs), and Focus Group discussions (FGDs). Qualitative analysis identified recurring themes. The circle of the leaders promotes the following: (1) professional development; (2) character development; and (3) collaboration with other school administrators.